Analisis Relativitas Khusus Dan Implikasi Pada Fisika Modern - Bu'ulolo, Wensy; Gea, Selvin Yulinda (CV. SINAR HOWUHOWU, 2024)
The physical theory of relativity opens up a new understanding of physics and cosmology. Since the beginning of human civilization, the discussion of cosmology has always been related to theological or divine aspects. The initial theory of cosmology is geocentric, that the earth is the center of the cosmos and the universe was created instantly by God. The classical understanding and interpretation of the Holy Scriptures of Abrahamic religions is considered to be in line with the geocentric theory. The heliocentric theory - the sun as the center of the cosmos - emerged in the 16th century, shifting the geocentric understanding. The heliocentric understanding makes the discussion of cosmology separated from theological concepts. There was a dichotomy between religion and science. The concept of creation re-emerged in the early 20th century after Einstein's theory of relativity became the foundation for understanding contemporary cosmology. This paper discusses the implications of the theory of relativity and the development of cosmology on the understanding of the Godhead or Contemporary Theology. The research paper uses qualitative research methods with a library research approach and the analysis developed uses descriptive analysis methods, with the concept of the integration of science and theology. The results of research on relativity that space and time are relative quantities, become the basis for understanding the theory of the development of the cosmos. In accordance with Hubble's law, the universe continues to grow and when traced backwards, the universe originated from the